Development and testing of air breathing fuel cell - Sim, Nicholas Jian Hao. (2011)
With the demand of energy for our daily needs ever increasing and the supply of fossil fuels (Earth main energy source) depleting fast and coupled with serious environmental effects, an alternative ‘clean source of energy’ is urgently required. Fuel cell can carry out electromagnetic reaction by taking Hydrogen gas as a fuel source and oxygen from the atmosphere as a reactant to supply electrical energy. Manufacturing process for fuel cell is relatively simple due to lack of mechanical movements and on top of that the cell also have longer operational period. Since the output of an ideal fuel cell is pure water and the emission are extremely low, thus making them an environmental friendly solution.